'How our forebears lived': the modern nation, its folklore and 'living' heritage in twentieth-century Australia. Issue 1 (2nd January 2018) - Darian-Smith, Kate; Nichols, David
ABSTRACT: This article examines the creation of the Swan Hill Folk Museum, which opened in 1966 following an upsurge of interest in Australia's pioneer and environmental history and heritage. Initially designed by the modernist architect Roy Grounds in collaboration with Eric Westbrook, the director of the National Gallery of Victoria, the Folk Museum offered an innovative interpretation of the past aimed to bolster regional development and tourism. We examine the genesis of the Folk Museum, later renamed the Swan Hill Pioneer Settlement, as a negotiation between local, regional and national narratives about the cultural, environmental and historical impacts of settler colonialism in Australia. The economic success of the Swan Hill Folk Museum in the 1960s and 1970s would inform the creation of numerous open-air pioneer museums throughout Australia during the second half of the twentieth century, and these shaped understandings of the histories, geographies and heritages of rural Australia.